Accountability in Nonprofit Governance: A Process-Based Study. (August 2017) - Tacon, Richard; Walters, Geoff; Cornforth, Chris
Accountability is a crucial element of governance. Nonprofit organizations are typically accountable to multiple stakeholders and often "do" accountability in multiple ways. But what happens when a nonprofit organization is highly dependent on a single source of funding? This article provides an empirical exploration of this issue. It draws on a longitudinal case study of one nonprofit organization in the United Kingdom that is highly dependent on a single funder to examine how accountability is constructed and enacted, with a focus on the board. It critically examines accountability processes through direct observation of board and committee meetings and in-depth interviews with board members. The analysis shows how board members work to construct broader forms of accountability beyond accountability to the funder, but then struggle to enact them. This article provides in-depth insight into the challenges that nonprofit board members face and offers a rare example of observational research on board behavior.